2016
DOI: 10.1186/s13054-016-1555-3
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of regulatory non-coding RNAs in sepsis: a systematic review

Abstract: BackgroundSepsis coincides with altered gene expression in different tissues. Accumulating evidence has suggested that microRNAs, long non-coding RNAs, and circular RNAs are important molecules involved in the crosstalk with various pathways pertinent to innate immunity, mitochondrial functions, and apoptosis.MethodsWe searched articles indexed in PubMed (MEDLINE), EMBASE and Europe PubMed Central databases using the Medical Subject Heading (MeSH) or Title/Abstract words (“microRNA”, “long non-coding RNA”, “ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 154 publications
5
80
0
1
Order By: Relevance
“…While highly accurate, the time to analysis can take days to weeks, whole genome sequencing is costly, and it can also identify commensals that may not be related to the disease. Deep sequencing technologies have also been used to determine epigenetic changes due to sepsis such as DNA methylation [58], histone modification [59], oxidative base damage [60] and mirRNA, ncRNA and mitochondrial RNA expression [61]. These emerging studies could provide unique insight in the disease process.…”
Section: System Biology Analysis Of Clinical Samples Provides Uniquementioning
confidence: 99%
“…While highly accurate, the time to analysis can take days to weeks, whole genome sequencing is costly, and it can also identify commensals that may not be related to the disease. Deep sequencing technologies have also been used to determine epigenetic changes due to sepsis such as DNA methylation [58], histone modification [59], oxidative base damage [60] and mirRNA, ncRNA and mitochondrial RNA expression [61]. These emerging studies could provide unique insight in the disease process.…”
Section: System Biology Analysis Of Clinical Samples Provides Uniquementioning
confidence: 99%
“…MicroRNA is known to be one kind of noncoding RNAs that can regulate specific genes expression posttranscriptionally by targeting their mRNAs. Recent studies have revealed that numerous microRNAs involved in the process of sepsis and associated immune suppression, organ malfunction, and metabolism dysregulation [18][19][20][21][22]. These microRNAs serve as either extracellular or intracellular effector molecules targeting special mRNAs to manipulate metabolism and function of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical processes for the biosynthesis of microRNAs. microRNA-124 interactions [130][131][132], microRNA-181 interactions [133][134], microRNA-10a interactions [135][136][137], microRNA-21 interactions [138][139][140][141][142], microRNA-92a interactions [142][143], microRNA-125b, microRNA-130a, microRNA-210 [144][145][146][147][148].…”
Section: Micrornas Expression In Sepsis-induced By Cannabinoid Signalmentioning
confidence: 99%